2017
DOI: 10.21037/gs.2016.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the decision to pursue immediate breast reconstruction after mastectomy for breast cancer

Abstract: Background: Immediate breast reconstruction (IBR) after mastectomy has shown to be oncologically safe and to improve quality of life in breast cancer patients. However, most women undergoing mastectomy do not undergo IBR. In this study, we aim to identify breast surgeon-related factors in considering IBR and factors affecting patients' decision to choose for IBR.Methods: Retrospective analysis of the records of breast cancer patients who underwent mastectomy with or without IBR between 2010 and 2013. We docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The Scottish guidelines suggest a target of 10% [ 18 ] and Singapore 20% [ 19 ] despite the well documented safety and psychological and emotional well-being related benefits [ 14 , 15 ]. A Dutch retrospective analysis found key factors inhibiting the decision making of IBR post mastectomy [ 22 ] included higher age (62.2 vs 51.9) and BMI (27 vs 24.3) and failure of surgeon to offer IBR due to predicted need for post mastectomy radiation (29.3%) or just failure of informing the patient (10%). In Australia reports of around 40% IBR rate have been achieved by some groups [ 20 ] with the main reasons not to have reconstruction being patient choice (45%) and surgeon’s perception of high-risk tumours (32%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Scottish guidelines suggest a target of 10% [ 18 ] and Singapore 20% [ 19 ] despite the well documented safety and psychological and emotional well-being related benefits [ 14 , 15 ]. A Dutch retrospective analysis found key factors inhibiting the decision making of IBR post mastectomy [ 22 ] included higher age (62.2 vs 51.9) and BMI (27 vs 24.3) and failure of surgeon to offer IBR due to predicted need for post mastectomy radiation (29.3%) or just failure of informing the patient (10%). In Australia reports of around 40% IBR rate have been achieved by some groups [ 20 ] with the main reasons not to have reconstruction being patient choice (45%) and surgeon’s perception of high-risk tumours (32%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…BR decision-making is a difficult choice often made by physicians alone 8 and, for IBR, made essentially considering medical factors. 4,5 Women's opinion is more important in delayed BR (ie, a BR performed after adjuvant treatments) decisionmaking. 41 Yet, as pointed out by Fasse et al 9 and Harcourt and Rumsey, 42 women and partners indicate that physicians have a central role in BR decision-making, for choosing between IBR and delayed BR, as well as the technique used to reconstruct the breast (ie, implant or autologous).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed to nearly 30% of women, 4 as this choice is essentially influenced by medical factors (eg, tumor localization or severity of the disease). 4,5 This treatment is supposed to be decided upon in a shared decision-making process between the patient and the physician, involving the family. The interprofessional shared decision-making model 6 highlights the interactions between the patient, health professionals, and family members to make a treatment choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study identified, among others, concerns regarding body image and the reduced burden of only a single operation as the reasons expressed by patients for favoring DR. Nevertheless, many women do not undergo DR after mastectomy for various reasons, including not having been offered or informed about DR [24]. Thus, the decisions for or against BCS and DR are preference-sensitive decisions for breast cancer patients, who should be able to make informed decisions together with their doctor by weighing the advantages and disadvantages of treatment options [25].…”
Section: Introductionmentioning
confidence: 99%